Ліпідний та білковий склад плазми крові щурів за умов експериментальної виразки шлунка - Кучеренко, М.Є.; Дворщенко, К.О.; Ковальова, В.А.; Дворщенко, О.С.; Моргаєнко, О.О.; Остапченко, Л.І. (Видавничий дім "Академперіодика" НАН України, 2007)
As a result of experimental ulcerogenesis, there are changes of the lipid and protein compositions in a blood plasma of rats. It is enriched by neutral lipids, and its content of phospholipids varied in different ways. Under stress ulcer, the fraction of proteins with a molecular weight of 23 kDа is revealed.